CMakeCatchTemplate: A C++ template project. (16th July 2021) - Dowrick, Thomas; Ahmed, Mian; Thompson, Stephen; Hetherington, James; Cooper, Jonathan; Clarkson, Matt
CMakeCatchTemplate ( https://github.com/MattClarkson/CMakeCatchTemplate ) is a project to provide a starting structure for C++ projects configured with CMake, that can be customised to work in a variety of scenarios, allowing developers to deploy new algorithms to users in a shorter timeframe. Main features include a SuperBuild to build optional dependencies; unit tests using Catch; support for CUDA, OpenMP and MPI; examples of command line and GUI applications; Doxygen integration; Continuous Integration templates and support for building/deploying Python modules.